Effect of the aqueous, acidic and alcoholic extract of dried leaves of Erythroxylum coca var. coca (coca) in Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis and Candida albicans in vitro - Luna-Vílchez, Medalit (2017)
Objective: To evaluate the effect of aqueous, acidic and alcoholic extract of dried leaves Erythroxylum coca var coca (coca) on Trichophyton rubrum (TR), Trichophyton mentagrophytes (TM), Microsporum canis (MC) and Candida albicans (CA) in vitro. Materials and methods: Experimental study, which evaluated the presence or absence of growth, the growth rate of fungi from the sowing point compared with their growth in Sabouraud Agar (AS). It was analyzed with Siegel-Tukey, Kruskal-Wallis, with p<0.05. Results: CA group found statistical difference (p<0.05) between groups ethanol 99.9% vs Aqueous, ethanol 99.9% vs HCl 0.01M, ethanol 99.9% vs control, control vs aqueous, HCl 0.01M vs control, TR group found difference (p<0.05) between groups ethanol 99.9% vs HCl 0.01M, ethanol 99.9% vs aqueous, ethanol 99. 9% vs control, HCl 0.01M vs control; TM group found difference (p<0.05) between the groups: ethanol 99.9% vs HCl 0.01M, ethanol 99.9% vs control, aqueous vs acid, aqueous vs control; MC group found difference (p<0.05) between the groups: ethanol 99.9% vs HCl 0.01M, ethanol 99.9% vs control, aqueous vs acid, aqueous vs control. In all cases the HCl 0.01M vs aqueous group was non-significant. Conclusions: The aqueous, acidic and alcoholic extracts have no effect on the growth of CA and TM but on TR and MC in alcoholic extract. In addition, there was a difference in the growth rate of CA, TR and TM in aqueous, acid and alcoholic extracts compared to AS, but among them only TR, TM and MC showed a difference in growth rate.